Understanding the political connections of Portuguese companies through their board members - Ferreira, P.; Oliveira, J.; Azevedo, G. (European Journal of Management Studies, 2024)
Purpose This study aims to analyse the political connections of Portuguese companies through the members of the board of directors, exploring how these connections influence, in particular, the composition and characteristics of the boards. Design/methodology/approach The research used a strategy based on analysing the financial statements and curriculum vitae of the directors of Portuguese companies listed on Euronext Lisbon from 2014 to 2019. The political connections of board members were examined, considering the variables identified in the existing literature. Findings The results indicate that companies with political connections maintain these relationships for long periods and have a greater number of members on the board of directors compared to companies without such connections. Directors with political experience tend to occupy non-executive positions, suggesting that companies may value political contacts more than the management skills of these directors. It was also found that there are politically connected directors who belong to multiple boards and that women appointed to the board are less likely to have a political background, reflecting male dominance in Portuguese politics. Research limitations/implications The main limitations of this study include the small number of listed companies in the sample, which may affect the statistical robustness of the results, as well as the use of secondary sources, which may not capture all relevant policy linkages. In addition, the results are specific to the Portuguese context and may not be generalisable to other countries or other regions of the world. Originality/value This study contributes to the understanding of political connections in Portuguese companies, offering valuable insights into how these connections influence board composition and can impact corporate strategy and governance. The findings of this study can be especially useful for business leaders looking to optimise the formation of their boards of directors.